Acute effects of a physically constraining tool on different phases of tennis serve technique - Busuttil, N. A.; Dunn, M.; Roberts, A. H.; Perrett, C.; Middleton, K. J. (Journal of Sports Sciences, 2025)
The purpose of this study was to compare upper-body kinematics of tennis players when modifying their grip position using a physically constraining tool during the tennis serve. Thirty right-handed tennis players performed serves using two grip position variations (preferred [Continental], grip-constrained [Precision-continental]) across two directions (Deuce, Advantage). Upper limb and racket trajectory data were captured with 60 reflective skin-attached markers using a 22-camera Vicon motion capture system (240 hz). Shot accuracy and racket kinematics were similar; however, the peak horizontal racket velocity was greater in the deuce condition. Significant main effects were observed at the dominant shoulder across grip type and shot direction, while grip-constrained serves featured increased elbow pronation and wrist ulnar deviation during the preparation and propulsion-acceleration phases. During the preparation phase, significant interactions between grip type and shot direction occurred for grip angle (17-40% of the phase) and elbow pronation/supination (0-5%, 65-77%), where the grip-constrained condition featured increased counterclockwise rotation (grip angle) and supination of ~ 3°. Using a physically constraining tool for acute grip modification appears to influence upper limb kinematics, with the magnitude possibly being serving direction-dependent.